2020
DOI: 10.1101/2020.02.28.970343
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Designing of a next generation multiepitope based vaccine (MEV) against SARS-COV-2: Immunoinformatics andin silicoapproaches

Abstract: 1Coronavirus disease 2019 (COVID-19) associated pneumonia caused by severe acute respiratory 2 coronavirus 2 (SARS-COV-2) was first reported in Wuhan, China in December 2019. Till date, 3 no vaccine or completely effective drug is available for the cure of COVID-19. Therefore, an 4 effective vaccine against SARS-COV-2 is needed to be design. This study was conducted to 5 design an effective multi-epitope vaccine (MEV) against SARS-COV-2. Seven antigenic 6 proteins were taken as a target and epitopes (B cell, I… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 91 publications
3
23
0
Order By: Relevance
“…Generally, a protein whose instability index is lesser than 40 are predicted to be stable and values above that predicts the protein as unstable [55]. The stability of the vaccine candidate in this study was found to be better than the recently published multiepitope vaccine candidate against SARS-CoV-2 in which instability index was found higher than the vaccine candidate of this study [56,57]. The theoretical pI of the vaccine was calculated to be 9.96.…”
Section: Immune Simulationmentioning
confidence: 65%
“…Generally, a protein whose instability index is lesser than 40 are predicted to be stable and values above that predicts the protein as unstable [55]. The stability of the vaccine candidate in this study was found to be better than the recently published multiepitope vaccine candidate against SARS-CoV-2 in which instability index was found higher than the vaccine candidate of this study [56,57]. The theoretical pI of the vaccine was calculated to be 9.96.…”
Section: Immune Simulationmentioning
confidence: 65%
“…Several vaccines for virus diseases were designed based on these approaches that include effective vaccines on Human papilloma viridea (HPV) [23],Ebola [24], Zika[25]and MERS[26, 27]viruses. There are also few reports of a vaccine candidate for COVID19[28, 29]. These vaccines contained multiple cytotoxic T lymphocytes (CTL) and B cell epitopes against several proteins of SARS-CoV-2 virus.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the multi-epitope vaccine involves fusion of multiple epitopes identified from the proteome of the SARS-CoV-2 by short peptide linkers. Several subunit and multi-epitope-based vaccine designs have been published claiming potential to activate CD4 and CD8 T-cell immune response driving long-term robust adaptive immunity in the vast majority of the population (Abdelmageed et al, 2020 ; Ahmed et al, 2020 ; Akhand et al, 2020 ; An et al, 2000 ; Banerjee et al, 2020 ; Baruah & Bose, 2020 ; Bhattacharya et al, 2020 ; Fast & Chen, 2020 ; Gragert et al, 2013 ; Gupta et al, 2020 ; Herst et al, 2020 ; Ismail et al, 2020 ; Khan et al, 2020 ; Lee & Koohy, 2020 ; Liu et al, 2020 ; Lu et al, 2014 ; Mitra et al, 2020 ; Nerli & Sgourakis, 2020 ; Poran et al, 2020 ; Ramaiah & Arumugaswami, 2020 ; Saha & Prasad, 2020 ; Sheikhshahrokh et al, 2020 ; Singh et al, 2020 ; Srivastava et al, 2020a ; 2020b ; Ul Qamar et al, 2020 ; Vashi et al, 2020 ; Yarmarkovich, Farrel et al, 2020; Yazdani et al, 2020 ). Numerous highly antigenic regions have also been reported from SARS-CoV-2 proteins, which have been recognized with a large population coverage by favorable binding with large number of HLA allele distributed among different ethnic human population across the world (Grifoni et al, 2020b ; Yarmarkovich, Warrington, et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%